. - Chin, Jean Lau(ed.) (London, 2004)
Prejudice and discrimination are not new. The legacy of the Pilgrims and early pioneers suggested a homogenous, mainstream America. Our early emphasis on patriotism in the United States resulted in a false idealization of the melting pot myth. Prejudice and discrimina tion in American society were overt and permeated all levels of society, that is, legislation, government, education, and neighborhoods. In the 1960s, attempts to eradicate prejudice, discrimination, and racism were explicit-with an appeal to honor and value the diversity within different racial and ethnic groups. This soon extended to other dimen sions of diversity, including gender, disability, and spirituality. How ever, long after the war to end slavery, the civil rights movement of the 1960s, desegregation in the schools, and the abolition of anti Asian legislation indeed, in the midst of growing public debate today regarding gay marriage-we still see the pernicious effects of prejudice and discrimination in U.S. society
Keywords: Prejudices-United States